2005
DOI: 10.1002/cm.20064
|View full text |Cite
|
Sign up to set email alerts
|

An electro‐optic monitor of the behavior of Chlamydomonas reinhardtii cilia

Abstract: The unicellular green alga Chlamydomonas reinhardtii steers through water with a pair of cilia (eukaryotic flagella). Long-term observation of the beating of its cilia with controlled stimulation is improving our understanding of how a cell responds to sensory inputs. Here we describe how to record ciliary motion continuously for long periods. We also report experiments on the network of intracellular signaling that connects the environment inputs with response outputs. Local spatial changes in ciliary respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…As flagellum-propelled movements are mercurial and remain poorly understood (29,47), we tentatively offer several speculations regarding the asynchrony and steering anomaly of RSP2 cells. This reminded us of the spinning tendency of a transgenic mutant defective in a calcium-binding motif of an outer dynein docking protein (9).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…As flagellum-propelled movements are mercurial and remain poorly understood (29,47), we tentatively offer several speculations regarding the asynchrony and steering anomaly of RSP2 cells. This reminded us of the spinning tendency of a transgenic mutant defective in a calcium-binding motif of an outer dynein docking protein (9).…”
Section: Discussionmentioning
confidence: 77%
“…The spokehead contacts the CP intermittently, and the contact is crucial for flagellar beating and synchrony (62,66). It has been shown that bright light selectively enhances the inherent asynchrony of only one (trans) flagellum of an algal cell (29,47). Perhaps RSP2's C-terminal tail and calmodulin strengthen the spokehead, constitutively or in a calcium-dependent manner, to regulate the asynchrony rate.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional motion can be inferred by slight adjustments in focus necessary during visual observation to bring different parts of each cilium into focus, also seen in previous work [Rüffer and Nultsch, 1991]. The relative phase changes to square-wave stimulation occurring between the anterior and posterior quadrants of a single cilium [Josef et al, 2005] suggests either a nonplanar motion or a change in the orientation at the base of the cilium that is proportional to absolute light intensity. The detector signal amplitude and, therefore, velocity recorded will reflect changes in the ciliary beat plane.…”
Section: à3mentioning
confidence: 96%
“…Signals from sensory transduction control gene expression, initiate internal biochemical signals, change the membrane potential, and perturb the cell away from its ionic homeostasis. Analysis of a number of measures of the ciliary beating response suggests that ciliary beating is controlled by multiple processes occurring in parallel [Josef et al, 2005a]. There are many light regulable inputs that can be concurrently modulated and multiple outputs that can be observed dynamically in real time as the cell makes decisions based on the regulated and internal inputs.…”
mentioning
confidence: 99%
“…2). The rhodopsin photoreceptors are stimulated with modulated green light (543 nm) and the movements of each cilium are recorded [Josef et al, 2005a]. Chlamydomonas phototaxis responses are quite time-invariant over the ciliary monitoring interval ($2-5 h), provided the system is adapted (conditioned) prior to recording.…”
mentioning
confidence: 99%